Deep Brain Stimulation in childhood-onset dystonia due to brain pathology. A long-term study. (March 2022) - Mandarano, Romina; Danieli, Alberto; Petacchi, Elisa; Di Pede, Chiara; Mondani, Massimo; Armellin, Maria Teresa; Facchin, Dina; Martinuzzi, Andrea
Abstract: Background: Pallidal Deep Brain Stimulation (DBS) is an established treatment option for isolated, inherited or idiopathic dystonia, however data on its safety and efficacy in other forms of dystonia are more limited. Objectives: Retrospective analysis of motor and non-motor outcomes in pediatric onset refractory dystonia due to static or progressive brain disorders in a cohort of patients with a DBS treatment duration ≥12 months. Methods: Multidisciplinary assessments including standardised scales/tests of motor function, pain, quality of life, cognition and language were carried out before implantation and longitudinally afterwards. Results: 9 patients were included, 7 had cerebral palsy. Mean age at implantation was 209 months ± 156, mean treatment duration 84 ± 37 months. DBS was well tolerated and positively affected both motor and non-motor functions. In particular, statistically significant improvements were documented in Burke-Fahn-Marsden Scale scores (- 19.9% p 0.01031) at 12 months and in long-term quality of life (+28.6%, p 0.0292). Conclusions: DBS may be a useful treatment option in generalized dystonia associated with brain pathology. Even when the motor benefits are limited, improvements in quality of life and non-motor functions, or the possible prevention of serious dystonia-related complications, may have a significant impact on overall clinical status. Highlights: One of the longest follow up reported on DBS and dystonia associated with brain pathology. Non-motor effects of DBS may only be evident during long-term follow-up. DBS may positively affect global clinical status even when observable improvement in motor symptoms are limited.